Coming in hot: a qualitative investigation into perceptions of parents and doctors of reasons for the presentation of children with fever to the emergency department in England - Bernie Carter; Enitan D Carrol; David Taylor-Robinson; Paul Moran; Courtney Franklin (BMJ Paediatrics Open)
Introduction Paediatric emergency department (ED) attendances and admissions in England are increasing. Fever is a common presenting problem for these attendances. Anxiety and misperceptions surrounding appropriate management of fever persist among parents. Little evidence exists on the pathways to ED for fever, and doctors’ perceptions of why parents present their child to the ED.Objectives To understand perceptions of parents and doctors of the reasons for ED presentation for children (0–18 years) with fever in England.Design This forms the first part of a qualitative study, using reflective thematic analysis.Participants 15 parents (12 mothers and 3 fathers) who had taken their febrile child to hospital (2015–2023), and 5 ED doctors (4 consultants and 1 resident doctor) who had experienced treating a febrile child in an ED in England.Methods Semistructured remote (Zoom) interviews were conducted (2022–2023).Results Reflexive thematic analysis facilitated investigation into current parental concerns regarding fever and decision-making leading to ED attendance. The overarching theme ‘factors influencing unscheduled care’ comprised four key themes that reflected the complex interplay between factors influencing parental decision-making to seek emergency care, at the individual and wider structural level. These were parental proficiency and experience; social networks and access to services; fever phobia, uncertainty and anxiety; and reassurance. Doctors also acknowledged the importance of these factors, such as reassurance and showing compassion and further indicated a persistent educational gap surrounding fever between doctors and parents.Conclusions We widen the evidence base of why parents attend ED for paediatric fever and their perceptions of other health services. Parents face challenges when seeking care and perceived ED as a last resort. Interventions to support parental decision-making and management of fever could help to alleviate these challenges, as well as potentially reducing the demand for emergency care.